An Empirical Analysis of the Effect of Agricultural Sector Determinants on Economic Growth in Sri Lanka - Anusha, P.; Vijesandiran, S. (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The role of agriculture has been significantly emphasized in improving the living standard of the population and the economic framework of any country. Agriculture has been an important sector in Sri Lanka which contributes 7.4% to the GDP, 25.5% of the total labor force, and 20.62% to the foreign earnings and Livelihood Avenue for 2.1 million households in Sri Lanka. The contribution of agriculture sector determinants food, forestry, fishery, and livestock: to the GDP shows a declining trend during the last four decades. Therefore, this study attempts to examine the effect of these determinants on economic growth from 1987 to 2019. Secondary data was extracted from the Central Bank of Sri Lanka. The Augmented Dickey-Fuller and Phillips-Perron unit root tests confirmed that all the variables are stationary only at I(0) and I(1) and ARDL (3,4,4,3,4) model. The findings of the Auto-Regressive Distributed Lag (ARDL) bound test show that livestock has a statistically significant impact on RGDP at a 5% significant level in the long run in Sri Lanka. The Error Correction version of the ARDL test found that a short run significantly positive effect of food production, forestry, and livestock on RGDP. Thus, the Sri Lankan government should prioritize in focusing on different subsector determinants to accelerate the economic growth in Sri Lanka. Further, Sri Lanka should take favorable policy decisions to ensure a sustainable agricultural system to challenge the future crises and shocks in the food safety of the population.